Efektivitas Lembaga Pelatihan Kerja Dalam Mengurangi Pengangguran Di Kabupaten Madiun - Imam Nurwedi; Slamet Muchsin; Afifuddin Afifuddin (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
The high unemployment rate in Madiun Regency, reaching 4.34% in 2024, surpassing the East Java Province average of 4.19%, indicates that effective policy interventions are needed, particularly job training programs. Using the case study of LPK Aclasindo Inti Persada. This research aims to evaluate the overview of the job training program, assess its effectiveness, and identify obstacles in its implementation in an effort to reduce unemployment rates. This study conducted qualitative research with a case study design. The purposive sampling technique was used to select informants, and the research population consisted of institution managers and community members who participated in the training. Data collection was conducted thru observation, interviews, and documentation. Meanwhile, data analysis was carried out using a qualitative descriptive method consisting of the stages of reduction, presentation, and conclusion drawing. The research results show that effective job training improves competence, readiness, and workforce absorption thru alignment with industry needs and partnerships with companies. However, the impact has not been optimal due to low community participation, limited access to information and training, and minimal work experience. Moreover, structural barriers such as the limited job market continue to restrict the contribution of training in reducing unemployment. The research conclusion states that the success of the program is not only measured by the quality of training and the absorption capacity of graduates but also considers the level of participation, available job opportunities, and public perception. Therefore, strengthening the synergy between training institutions, the government, and the industrial sector, along with increasing outreach to the community, is key to building a sustainable and impactful job training model.